Mean Reversion of Low and High Stock Returns - Choi, B. Paul; Jeong, Jin-Gil; Mukherji, Sandip (Journal of Accounting and Finance, 2023)
This study investigates mean reversion of low and high stock returns for one- to ten-year periods, using 1,000 random block bootstraps. Regressions of later returns against prior returns of large-cap stocks indicate that high returns generally exhibit more significant mean reversion than low returns. Small-cap stocks display greater mean reversion of high returns for two to four years and low returns for five to ten years. Small-cap stocks show much stronger and more persistent mean reversion in returns than large-cap stocks. Both large- and small-cap stocks, however, provide substantially higher returns following low returns and lower returns following high returns.